Controlled Wave-Particle Interaction and VLF Wave Propagation Experiments in the Outer Magnetosphere. - Koons,H C (1981)
VLF transmission experiments were conducted from sites in North Norway during selected time periods in 1978, 1979 and 1980. Data from these experiments were collected from VLF receivers aboard the SCATHA (P78-2) and GEOS satellites and VLF receivers on the ground at various locations in Norway and Sweden. Direct signals were measured at each of the ground stations and emissions triggered by the transmissions were detected by the satellite receivers. This report documents the impedance measurements made on each of three power lines used as VLF antennas and summarizes the preliminary results from the VLF receiver data. (Author)